A Purr-Suasive Case for Sterilization: How Sterilizing Working Cats Supports Dairy Farmers’ Wellbeing, Improves Animal Welfare, and Benefits the Environment - Caitlin Crawford; Jacquie Rand; Olivia Forge; Vanessa Rohlf; Pauleen Bennett; Rebekah Scotney (Animals)
Rodents on farms are a substantial issue due to the damage they cause to produce and infrastructure, and the risk they pose to food safety. As a result, farmers need to control rodent populations around farms. In a previous study, farmers indicated a preference for working cats, stating that they are a more efficient, safer, and cheaper alternative to rodenticide baits, and they provide companionship. However, farmers’ options for managing cat populations are often limited to lethal methods because of time and financial constraints. Through semi-structured interviews, this study explored the impacts of lethal cat management methods on farmers, their experience with a free cat sterilization program, and their views on a Barn Cat Program, whereby healthy stray cats would be vaccinated, sterilized, and made available to farmers. Our results indicated that farmers had a relationship with the cats on their farms and that using lethal methods to manage these cats had a negative impact on farmers’ wellbeing. Farmers supported the free cat sterilization program, as it reduced the cat population and their impact on wildlife, improved cat behavior and welfare, and benefited farmers. Farmers also generally supported a Barn Cat Program and gave suggestions on how best to promote it to other farmers. Funding should be provided for cat sterilization programs, as they support farmers, who value cats for rodent control and companionship, improve cat behavior and welfare, and reduce working cat populations and their impact on wildlife.